PENGARUH BID-ASK SPREAD, MARKET VALUE, VARIANCE RETURN SAHAM, DAN RETURN ON EQUITY TERHADAP HOLDING PERIOD PERUSAHAAN LQ-45 PERIODE 1999-2002 - NURUL IMAN (2004)
The ideas of this research arose from different results between Atkins and Dyl (1997), and Lenny and Indriantoro (1999). Atkins provided results that higher spreads were held by investors for longer holding periods, but Lenny's research said that market values were significant with holding periods. The different results were possibly caused by the different condition of market. Lenny's research used Jakarta Stock Exchange (JSX) and Atkins used NYSE and Nasdaq. The objective of this research was to test their results by using bid-ask spreads, market values, variance returns, and return on equities with holding periods for common stocks from 1999 to 2002 in Jakarta Stock Exchange (JSX). This research was to answer the question: do bid-ask spreads, market values, variance returns, and return on equities influence holding period ? The statistical method used in this research was two stage least squares multiple regression, then regression coefficient, F-test, and t-test on 5% level of significant, by using SPSS version 11.0. Samples were taken from the company's stocks that in 1999-2002 were always or ever been listed as Liquid-45. The statistical result showed that bid-ask spreads, market values, variance returns, and return on equities could not be used to predict the holding periods, nevertheless the bid-ask spreads and market values were positive and significant.